A Mobile-Based Stocktaking Program and Dashboard Application for Monitoring Packaging Stock at PT. Pangan Terbaik Indonesia, Jakarta - Sukendar, Toni; Achmad Sumbaryadi; M. Ikhsan Saputro; Ahmad Ishaq; Rame Santoso (Jurnal Teknologi Informatika dan Komputer, 2025)
In today's digital age, the effectiveness and accuracy of inventory management are crucial factors in a company's operations. Manual inventory recording is often time-consuming, error-prone, and inefficient in presenting data directly. The problem at PT Pangan Terbaik Indonesia is that the company's director is unaware of the current packaging stock available in the warehouse. This is because inventory recording is not done in real time, still using manual calculations and paper recording. This prevents the director from monitoring the warehouse's inventory in real time, leading to concerns about stockouts or excess inventory. Furthermore, the company's website is not currently integrated with a database, which can be a hassle for the administrator if there are changes to the website data. The purpose of designing the stocktaking system itself is to simplify the stock recording process, allowing field officers to record packaging stock using a mobile application, and the data will be stored in the database and can be viewed in real time by the company director. This also simplifies website management. With integration with the database, the company administrator can easily change company data through the admin dashboard. The result of this report is to design an application that makes it easier for companies to record stock, manage company information, and monitor stock data in real-time so that reports are received more quickly and accurately.